PENGARUH WAKTU AERASI TERHADAP LIMBAH KEDELAI MENGGUNAKAN BAKTERI Pseudomonas Putida - Rofiq Sunaryanto; Nur hayati (JURNAL TECHLINK, 2023)
Industrial liquid waste in liquid form resulting from tempe production can pollute the environment which is detrimental to the surrounding community. According to the World Health Organization (WHO), waste is the result of human activities that are useless, not used or something that is thrown into the environment. Tempe industrial wastewater is very disturbing to waters if it is not managed properly before being discharged into water bodies because this waste causes an unpleasant odor and triggers the growth of various pathogenic bacteria. If the waste is directly disposed of into the waters, in a relatively short time it will cause a foul odor from H2S gas or ammonia as a result of the crying of the organic waste. The existence of a decomposition process will cause an unpleasant odor (Wiryani Erry, 2012). The process of making tempeh in each of its stages uses an average of water for washing, soaking, and boiling the soybeans. This means that quite a lot of liquid waste is produced. This study aims to analyze the content of soybean liquid waste to reduce BOD levels to make it more environmentally friendly. With the aim of reducing BOD levels, this study will use the Pseudomonas Putida bacterium as a waste decomposer, bioreceptors and microelectrodes as practical BOD measuring devices. The sample used is boiled liquid waste from soybean skin in the process of making tempe at one of the tempe entrepreneurs near the Satya Negara University of Indonesia. The sample was then tested to see the content of DO, BOD, temperature, pH, TDS, and total bacteria. The results of research on soybean liquid waste showed that the content of BOD and TDS exceeded the quality standards set by the Regulation of the State Minister for the Environment 03 of 2010 concerning the Environment.